2023
DOI: 10.15585/mmwr.mm7246e1
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs: Missed Opportunities for Preventing Congenital Syphilis — United States, 2022

Robert McDonald,
Kevin O'Callaghan,
Elizabeth Torrone
et al.

Abstract: Introduction Congenital syphilis cases in the United States increased 755% during 2012–2021. Syphilis during pregnancy can lead to stillbirth, miscarriage, infant death, and maternal and infant morbidity; these outcomes can be prevented through appropriate screening and treatment. Methods A cascading framework was used to identify and classify missed opportunities to prevent congenital syphilis among cases reported to CDC in 2022 through the National Notifiable Diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Independent factors that contributed to the lack of screening included basic or lower level of education, low socioeconomic status, serving as head of household, single marital status, and accessing prenatal care in the second or third trimester of pregnancy. Similar findings on socioeconomic level, prenatal care access, and compliance with screening were reported in the United States ( 20 , 31 ). In Colombia, late entry into prenatal care was associated with a low socioeconomic stratum ( 32 ), and a study in China found that single mothers (aOR 1.95) and women who had inadequate prenatal care (aOR 3.61) were at increased risk of having infants with congenital syphilis ( 30 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Independent factors that contributed to the lack of screening included basic or lower level of education, low socioeconomic status, serving as head of household, single marital status, and accessing prenatal care in the second or third trimester of pregnancy. Similar findings on socioeconomic level, prenatal care access, and compliance with screening were reported in the United States ( 20 , 31 ). In Colombia, late entry into prenatal care was associated with a low socioeconomic stratum ( 32 ), and a study in China found that single mothers (aOR 1.95) and women who had inadequate prenatal care (aOR 3.61) were at increased risk of having infants with congenital syphilis ( 30 ).…”
Section: Discussionsupporting
confidence: 82%
“…A newborn with congenital syphilis was any live birth or stillbirth that met > 1 of the following criteria: newborns of a mother with untreated syphilis or inadequate treatment (without > 1 dose of BPG > 30 days before delivery) to prevent congenital syphilis ( 9 , 19 , 20 ), regardless of the result of the nontreponemal test of the newborn; any newborn with nontreponemal test titers 4 times higher than the mother’s titers at the time of delivery, which is equivalent to 2 dilutions above the maternal titer; any newborn of a pregnant person whose syphilis was diagnosed during that pregnancy and with > 1 clinical manifestations suggestive of congenital syphilis on physical examination, along with paraclinical tests suggestive of the infection; or any newborn with demonstrated T. pallidum in laboratory tests ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…5,15,[17][18][19] Treatment less than 30 days before pregnancy outcome might relate to patient-specific barriers and lack of awareness among clinicians about the need for These findings support recent CDC proposals to perform recommended syphilis screening during pregnancy outside of traditional prenatal care, including in emergency rooms, substance use treatment facilities, carceral settings, and homeless shelters. 10 Given challenges with accessing care across the United States-especially among people experiencing homelessness, incarceration, or substance use disorder -broader availability of rapid testing (ie, point of care) with immediate treatment is critical. Additionally, systems-based solutions, such as the use of pregnancy laboratory panels in other encounters and employing electronic health record notifications when syphilis testing or treatment are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A 2023 study of nationally reported congenital syphilis cases found that 51% were attributed to inadequate treatment despite a timely diagnosis during pregnancy, and 37% were attributed to a nontimely testing. 10 The objective of this analysis is to examine missed opportunities for congenital syphilis prevention by describing characteristics of peo-ple with syphilis during pregnancy that are associated with the lack of complete treatment during pregnancy.…”
mentioning
confidence: 99%
“…5 In that year, the Centers for Disease Control and Prevention, in close collaboration with state, local, and territorial health departments, began the 5-year initiative that has since produced several reports on congenital syphilis and missed opportunities for prevention. [6][7][8] Each time, the reports get more dire.…”
mentioning
confidence: 99%